(untitled) (Scientia Agropecuaria, 2022)
3D bioprinters present techniques that have various applications in the food industry. For this reason, this work aims to compile and review various research works focused on the utilities and advantages of this type of machinery. Where we first mention the basis of these bioprinting techniques and then proceed to highlight the bioethical issues that surround their application in the food industry, analyze the current advantages and disadvantages, the user that has been given in the production of food for astronauts, and also mention some of the research that has been taking place in Latin America and the world. The greatest advantage of 3D bioprinting of food is the speed of production compared to traditional manufacturing methods, allowing one to obtain food with various geometric shapes; it allows control of the nutritional value, and the texture of the product, reduces environmental pollution and has the advantage of being able to take advantage of the greater performance of the materials required for production. Additionally, this technology is considered an alternative production technique that will be used to solve the problem of feeding in places of scarce resources such as space and areas not suitable for animal husbandry.